Factors Influencing Juvenile Delinquency Using Betty Neuman's Nursing Theory With The Community As Partner (CAP) Approach In High School N 10 Purworejo: Faktor-Faktor Yang Mempengaruhi Kenakalan Remaja Menggunakan Teori Keperawatan Betty Neuman Dengan Pendekatan Community As Partner (CAP) di SMA N 10 Purworejo - Afriyanti, Tina; Marsito, M (Prosiding University Research Colloquium, 2023)
The adolescent population in Indonesia is based on the composition of the population by age group and sex with an estimated age of 18-23 years around 74.93% or 74.93 million people. Meanwhile, in Central Java the number of residents by region, generation classification, and gender obtained data that 9.3 million people are groups with an age range of 18-23 years. The number of adolescent population is quite high. The high adolescent population can increase adolescent problems or what is commonly known as juvenile delinquency.Knowing the factors that influence juvenile delinquency using Betty Neuman's theory with the community as partner approach at SMA N 10 Purworejo. This type of research is quantitative with a descriptive observational design. The research instrument used a Basic Life Support knowledge questionnaire. Sampling with a purposive sample. The research respondents were 212 people. The results of this study are the physical environment with a high category of 64.4%, health and social services with a medium category of 53.9%, the economy with a medium category of 93.2%, security and transportation with a medium category of 95.5%, politics and government with a medium category of 93.5%, communication with a medium category of 63.9%, education with a medium category of 62.4% and recreation with a high category of 55.4%. Factors that influence delinquency such as the physical environment, health and social services, economy, security and transportation, politics and government, communication, education and recreation with high results, namely the physical environment and recreation. Applying Betty Neuman's nursing theory approach using community as partner can be used to determine the factors that influence juvenile delinquency at SMA N 10 Purworejo.